Structure-phase states of the metal surface and undersurface layers after the treatment by powerful ion beams; Surface and Coatings Technology; Vol. 105, iss. 1-2 - Korotaev A. D.; Ovchinnikov S. V.; Pochivalov Yu. I.; Tyumentsev A. N.; Shchipakin D. A.; Tretjak M. V.; Isakov I. F.; Remnev G. E. Gennady Efimovich (1998, 1998)
Title screen